Dietary patterns and micronutrients in respiratory infections including COVID-19: a narrative review - Zahra Salehi; Mohammadreza Askari; Alireza Jafari; Batoul Ghosn; Pamela J. Surkan; Mohammad Javad Hosseinzadeh-Attar; Hamed Pouraram; Leila Azadbakht (BMC, 2024)
Abstract Background COVID-19 is a pandemic caused by nCoV-2019, a new beta-coronavirus from Wuhan, China, that mainly affects the respiratory system and can be modulated by nutrition. Methods This review aims to summarize the current literature on the association between dietary intake and serum levels of micronutrients, malnutrition, and dietary patterns and respiratory infections, including flu, pneumonia, and acute respiratory syndrome, with a focus on COVID-19. We searched for relevant articles in various databases and selected those that met our inclusion criteria. Results Some studies suggest that dietary patterns, malnutrition, and certain nutrients such as vitamins D, E, A, iron, zinc, selenium, magnesium, omega-3 fatty acids, and fiber may have a significant role in preventing respiratory diseases, alleviating symptoms, and lowering mortality rates. However, the evidence is not consistent and conclusive, and more research is needed to clarify the mechanisms and the optimal doses of these dietary components. The impact of omega-3 and fiber on respiratory diseases has been mainly studied in children and adults, respectively, and few studies have examined the effect of dietary components on COVID-19 prevention, with a greater focus on vitamin D. Conclusion This review highlights the potential of nutrition as a modifiable factor in the prevention and management of respiratory infections and suggests some directions for future research. However, it also acknowledges the limitations of the existing literature, such as the heterogeneity of the study designs, populations, interventions, and outcomes, and the difficulty of isolating the effects of single nutrients from the complex interactions of the whole diet.